Between-match variation of peak match running intensities in elite football - Thoseby, Bradley; D. Govus, Andrew; C. Clarke, Anthea; J. Middleton, Kane; J. Dascombe, Ben (Biology of Sport, 2022)
Peak match running intensities have recently been introduced to quantify the peak running demands of football competition, across incremental time intervals, to inform training practices. However, their between-match variation is yet to be comprehensively reported, limiting the ability to determine meaningful changes in peak match running intensities. The current study aimed to quantify the between-match variability in peak match running intensities across discrete moving average durations (1–10 min). GPS data were collected from 44 elite football players across 68 matches (mean ± SD; 13 ± 10 observations per player). For inclusion players must have completed 70mins of a match across a minimum of two matches. Performance metrics included total and high-speed (> 19.8 km·h-1) running distances and average acceleration (m·s -2), expressed relative to time. For each metric, the coefficient of variation and smallest worthwhile difference were calculated. The peak match running intensity data was similar to previously reported data from various football competitions. The between-match CV of relative total distance ranged between 6.8–7.3%, with the CV for average acceleration and relative high-speed running being 5.4–5.8% and 20.6–29.8%, respectively. The greater variability observed for relative high-speed running is likely reflective of the varying constraints and contextual factors that differ between matches. The reported between-match variability helps to provide context when interpreting match performance and prescribing training drills using peak match running intensity data.